SEJARAH PERKEMBANGAN KALKULUS OLEH ISAAC NEWTON DAN GOTTFRIED LEIBNIZ - Eka Damayanti; M. Riyan Afandi; Murima Amanah Wanti (UPT Penerbitan Universitas Jember, 2022)
In today's modern era, who is not familiar with calculus? Currently, calculus has become a necessity in technological progress. The development of calculus technology became one of the driving factors in the emergence of software - software both on smartphones and computers. One of them is a specific integral function of one variable to calculate the area of ​​a flat area bounded by curves. This calculation is beneficial for several fields such as cartography, physics, and even the field of computer science. Not only that Calculus is also used in every branch of physical science, computer science, statistics, engineering, economics, business, medicine, population, and other fields. Along with the development of calculus, its history was discovered and even developed by various world geniuses such as Isaac Newton and Gottfried Leibniz. In this case, we will discuss how the history of the development of calculus. Keywords: Kalkulus, Leibniz, Newton